An analysis of short put strategies and their role in asset allocation. Issue 3 (3rd July 2018) - Schwalbach, João Bruno Meneses; McClelland, David
ABSTRACT: Fully-collateralised short put strategies have been found by Ungar and Moran (2009) to have similar return and improved risk characteristics when compared to broad market ETF equity exposure, resulting in an improved risk-return relationship. This paper analyses the risk and return characteristics of multiple fully-collateralised short put strategies, varying by moneyness and maturity, and the impact of introducing these strategies to the traditional 60/40 equity/bond mix. The findings indicate that greater time-to-maturity generally reduces returns and increases risk, making the shorter 30-day strategies superior. Incrementally changing the level of moneyness from 10% out-of-the-money (OTM) to 2.5% in-the-money (ITM) increased returns up until 2.5% ITM, at the expense of increasing risk and drawdown monotonically. When viewing the strategy as part of a wider asset allocation decision, the OTM strategies in general displayed much lower correlations with equity than their ATM or ITM counterparts. Specifically, the greatest risk/return performance was achieved at 5% OTM contract strategies, suggesting that OTM strategies complement equity holdings. This was verified when the traditional 60/40 equity/bond portfolio was compared to an equivalent portfolio which replaced half of the equity holdings with various short put strategies.